Mandibular bone remodeling after natural collagen transplantation: histological, immunohistochemical and ultrastructural aspects - Chelpanova , I.V. (Морфологія / Morphologia / Morfologìâ, 2023)
This article presents the research results of the histological, immunohistochemical, and ultrastructural characteristics of bone-ceramic regenerate after natural collagen transplantation into an experimental defect in the rabbit mandible, since complete and high-quality regeneration of maxillofacial bones, its mechanisms and dynamics remain not fully understood, need clarification and detailing. Aim. To study in an experiment the dynamics of histological, immunohistochemical, and ultrastructural changes in the lower jaw bone after its traumatic injury with subsequent replacement of the defect with natural collagen. Methods. Experiments were conducted on 89 male rabbits aged 6-7 months, weighing 2.5-3.0 kg. 20 animals constituted the control group, and 64 the two experimental groups. Another 5 intact animals were used to study the normal structure of the bone tissue of the studied area of the mandible. The control group included animals with a bone tissue defect that healed under a blood clot. The first experimental group consisted of 32 rabbits where the bone defect was filled with modified natural collagen (Col-C). The second experimental group consisted of 32 rabbits where the bone defect was filled with natural collagen, , with simultaneous intramuscular injection of Lincomycin at a dose of 12 mg/kg of animal weight once daily for 6 days (Col-C-Lincomycin). Post-traumatic bone tissue status within the defect area was monitored for 84 days using the following methods: bone defect modeling, light-optical assessment of the histostructure of decalcified bone sections, immunohistochemical determination of the expression of markers CD34, Calcitonin, Ki-67, transmission electron microscopy. Results and conclusion. Augmentation of the experimental defect using natural collagen results in intensive stimulation of neovascularization and the formation of numerous islands of desmal osteogenesis not only at the periphery but also in the inner regions of the regenerate. However, periosteal regeneration on the surface of the implanted material proceeds at a restrained pace during the first three weeks of the experiment. During this period, against a background of persistent inflammatory infiltration, the osteoconductive effect of the collagen implant is realized through the formation of a developed spongy structure of woven bone trabeculae due to the active migration of osteoprogenitor cells and the high mitotic and synthetic activity of clustered osteoblasts, although their degree of maturation remains limited. Due to the predominance of proliferative dynamics (based on the study of Ki-67 and CD34 marker expression) over the rate of osteogenic cell maturation, five weeks post-implantation the bone regenerate is a dense network of woven bone trabeculae with isolated loci of remodeling and without compaction signs. In the first three weeks post-implantation, the osteoconductive potential of exogenous collagen is manifested by accelerated vascularization of the peripheral and deep zones of the regenerate, enhanced migration and proliferation of poorly differentiated fibroblast and osteoblast precursors, and a significant increase in the number and density of membranous osteogenesis foci Between weeks 8 and 12 post-implantation of natural collagen, against a background of osteoclast activation, trabecular remodeling occurs synchronously throughout the osteoregenerate. Gradual compaction and mineralization of the lamellar bone tissue leads to the formation of a primitive lacuno-canalicular system, ensures significant but incomplete osteointegration of the regenerate, is accompanied by a reduction in the proliferative activity of fibroblast and osteoblast differentiating cells, maturation of most osteocytes, and stabilization of the overall histoarchitecture of the osteoregenerate.